2004
DOI: 10.1088/0960-1317/15/1/025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and squeeze film gas damping of a capacitive RF MEMS switch

Abstract: We report on measurements of the time dependent capacitance of a RF MEMS shunt switch. A high time resolution detection setup is used to determine switching time and motion of the device. From the equation of motion the damping force is extracted. The measured damping force is found to be approximately proportional to the speed over the gap distance to the third power (F D ∝ v/z 3 ), in good agreement with squeeze film damping theory. Measurements at low pressure show underdamped harmonic oscillations in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…At sweep rates above 500 V/s, the inertia of the RF-MEMS switch appears in the C-V characteristic [12]. The pull-in and pull-out voltages are then incorrectly deduced from the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…At sweep rates above 500 V/s, the inertia of the RF-MEMS switch appears in the C-V characteristic [12]. The pull-in and pull-out voltages are then incorrectly deduced from the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…3 and to Table I, the integration for obtaining the value of k to be used in Eq. (11) has been performed by choosing x 1 and x 2 by means of a coordinate system having the origin on the left side of the bridge. In this way, for the central actuation, x 1 =L/2 and x 2 =(L/2)+(L c /2); because of the symmetry of the analyzed structure, the integration is performed only on half of the length where the force is applied, and multiplied by a factor two (see Eq.…”
Section: One-dimensional Model Of the Mechanical Response Of Shunt Camentioning
confidence: 99%
“…The actuation as well as the de-actuation are affected also by the presence of a medium (typically air, or preferably nitrogen for eliminating humidity residual contributions in a packaged device) which introduces its own friction, causing a damping, and altering the speed of the switch [5]- [7]. Several models are currently available to account for a detailed treatment of the damping, including also the presence of holes in the metal beam [8]- [11]. Moreover, the damping modifies the natural frequency of oscillation for the bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey and Pratap [11] studied the effect of squeeze film damping under the effect of gas rarefaction and surfaces roughness; they observed that rarefaction lowers damping force without affect spring force significantly, but in presence of a high surface roughness and amplitude vibration, both damping and spring forces increases considerably. Steeneken et al [12] studied the dynamic behaviour of a capacitive RF shunt switch by extracting its motion from a capacitance measurement at high time resolution and comparing results with analytical and numerical ones. An other comparison between squeeze film damping effects on an inertial sensor at high and low pressure of surrounding fluid is performed by Braghin et al [13], that used a multi-physic code for numerical simulations and experimental measurements.…”
Section: A Somà G De Pasquale Identification Of Test Structures Fomentioning
confidence: 99%